PROTEIN AND OPIOID ANALYSIS BY CAPILLARY ELECTROPHORESIS WITH LASER INDUCED FLUORESCENCE AND MASS SPECTROMETRY DETECTION - Isbell, Theresa Ann (Wake Forest University, 2014)
Capillary electrophoresis (CE) has been recently used for the analysis of peptides and proteins, drugs and their metabolites, biological extracts, and environmental samples. The popularity of this technique arises from its ability to use very small sample volumes while still producing fast, highly efficient separations. In this dissertation two applications of CE are documented. The first application is the characterization of dyeprotein interactions for the purpose of developing efficient and sensitive assays for the separation and determination of proteins in complex sample mixtures. By examining the spectroscopic characteristics of dye-protein complexes we can better understand the types of interactions occurring within the complex, which can lead to better dye designs. With optimized dyes as protein probes, we are then poised to develop separation and quantification methods through the use of CE with laser-induced fluorescence detection (LIF). Optimal labeling and separation methods utilizing four novel asymmetric squarylium dyes as universal protein probes are presented herein. SQHN-1, -1a, and -1b have the same asymmetric structure with a single pendant carboxylic acid group tethered by increasing hydrocarbon chain length whereas the structure of SQID-1 contains a carboxylic acid group. All four dyes were found to be successful non-covalent labels for bovine serum albumin BSA, transferrin, and -lactoglobulin B and were also used in the separation of a complex mixture of these proteins. The slight differences in dye structures affected spectroscopic characteristics and also optimal CE-LIF conditions, including separation buffer. The second application is method development for the determination of morphine and its isobaric metabolites morphine-3-beta-D-glucuronide (M3G) and morphine-6-beta-D-glucuronide (M6G) by CE with time-of-flight mass spectrometry (CE-ESI-QTOF-MS). Limits of quantitation in normal human urine were found to be 1.0 µg/mL for morphine and 2.5 µg/mL for each of M3G and M6G. Patient samples (N=12) were analyzed by this new CE-ESI-QTOF-MS method and a 7% difference in total morphine content (relative to prior high performance liquid chromatography-mass spectrometry LC-MS results) was found, which was not significant as per a paired-t test at the 99% confidence level. The prior LC-MS method required enzymatic hydrolysis of the glucuronides and hence was only able to determine the total morphine species concentration, whereas the new CE-ESI-QTOF-MS method described herein allowed for species differentiation in addition to total morphine determination. By this method, it was found that M3G and M6G metabolites were present, on average, in a 5:1 concentration ratio in each of the patient samples. Therefore, the CE-ESI-QTOF-MS method not only allows for total morphine concentration determination comparable to established LC-MS methods, but also allows for differentiation between morphine and its glucuronides, yielding additional biochemical information about drug metabolism.